Bridging knowledge systems to enhance governance of environmental commons: A typology of settings - Rathwell, Kaitlyn Joanne; Armitage, Derek; Berkes, Fikret (International Journal of the Commons, 2015)
We offer a typology of settings to bridge scientific and indigenous knowledge systems and to enhance governance of the environmental commons in contexts of change. We contribute to a need for further clarity on how to incorporate diverse knowledge systems and in ways that contribute to planning, management, monitoring and assessment from local to global levels. We ask, what settings are discussed in the resource and environmental governance literature to support efforts to bridge indigenous and scientific knowledge systems? The objectives are: 1) to offer a typology that organizes various settings to bridge knowledge systems; and 2) to elaborate on how these settings function independently and in concert, using examples from a diverse literature in addition to field research experience. Our focus is on indigenous and scientific knowledge, but the typology offers lessons to bridge diverse knowledge systems more generally, and in ways that are sensitive to a moral, political and process-based approach. The typology includes specific methods and processes, brokering strategies, governance and institutional contexts, and the arena of epistemology. We describe each setting in the typology, and provide examples to reflect on the function and potential outcomes of different settings. Insights from our synthesis can inform policy and participatory action.